The factor structure of assaultive behaviour among acute schizophrenia patients - Bezdíček, Ondřej (The journal of forensic psychiatry & psychology, 2022)
Our primary goal was to determine the sources of assaultive behaviour in acutely psychotic patients. To find a few underlying structures for many different questions regarding assaultive behaviour based on Nolan’s semi-structured interview, the Assaults Interview Checklist (AIC), we used factor analysis. Data of 289 psychiatric patients in acute psychotic states perpetrating 820 assaultive attacks were analysed using the polychoric correlation matrix of the AIC items and exploratory factor analysis (EFA). We found five independent factors, i.e. underlying structures of assaultive behaviour: Predatory factors, Personality, Acute psychosis, Contextual Factors, and Cognitive control with high factor loadings explaining an overall 69% of the variance in the acute psychotic assaults. In women, the largest factor loadings were in Personality with Predatory/Psychopathic factors second, whereas in men Psychotic with Predatory gains played the prominent role. We interpret current findings in the framework of the triarchic theory of aggression in psychosis (psychotic, impulsive and predatory/psychopathic) when Predatory factors are dominant with interrelated facets of Personality and Contextual factors, whereas Acute psychosis contributes to psychotic and Cognitive control to impulsive factors. Surprisingly, our analyses show the possible evolutionary role of aggression (co-opting the resources of others) even in an acute psychotic state.